Formulation and evaluation of controlled porosity osmotic pump for oral delivery of valsartan - P.Vinay Kumar; K.Ashwin Kumar; D.Karthikeyan (International Journal of Pharmacy and Analytical Research, 2022)
The aim of the present study was to design a controlled porosity osmotic pump tablet of Valsartan. The controlled porosity osmotic pump tablet contains opdry CA as semipermeable coat form contact with water, dissolve, resulting in an in situ formation of a microporous structure. The dosage regimen of Valsartan is 80-350mg tablet 2-3times a day. The plasma of life ranges from 6-7hrs.Hence Valsartan was chosen as a model drug with an aim to develop a controlled release system for a period of 24hrs.The effect of different formulation variables. It was found that drug release was directly related to the amount of osmogent and level of pore former. The optimized formulation was subjected to stability studies as per international conference on harmonization (ICH) guidelines and formulation was stable after 3 months study.